Talmudic transgressions : engaging the work of Daniel Boyarin - Fonrobert, Charlotte Elisheva.; Rosen-Zvi, Ishay.; Shemesh, Aharon.; Vidas, Moulie, 1983-; Boyarin, Daniel. (Supplements to the Journal for the Study of Judaism, 2017)
Talmudic Transgressions is a collection of essays on rabbinic literature and related fields in response to the boundary-pushing scholarship of Daniel Boyarin. This work is an attempt to transgress boundaries in various ways, since boundaries differentiate social identities, literary genres, legal practices, or diasporas and homelands. These essays locate the transgressive not outside the classical traditions but in these traditions themselves, having learned from Boyarin that it is often within the tradition and in its terms that we can find challenges to accepted notions of knowledge, text, and ethnic or gender identity. The sections of this volume attempt to mirror this diverse set of topics. Contributors include Julia Watts Belser, Jonathan Boyarin, Shamma Boyarin, Virginia Burrus, Sergey Dolgopolski, Charlotte E. Fonrobert, Simon Goldhill, Erich S. Gruen, Galit Hasan-Rokem, Christine Hayes, Adi Ophir, James Redfield, Elchanan Reiner, Ishay Rosen-Zvi, Lena Salaymeh, Zvi Septimus, Aharon Shemesh, Dina Stein, Eliyahu Stern, Moulie Vidas, Barry Scott Wimpfheimer, Elliot R. Wolfson, Azzan Yadin-Israel, Israel Yuval, and Froma Zeitlin.